The impact of L1 literacy on the production of Spanish verbal passives by school-age Spanish heritage speakers - Armstrong, Andrew; Montrul, Silvina (Frontiers in language sciences, 2025)
Acquiring literacy contributes to monolingual children's language development, especially with the oral production of complex sentences. However, less is known about how written language exposure impacts first language (L1) morphosyntactic growth in Spanish-speaking children in the U.S., who are educated in their second language (L2) and have little opportunities to develop L1 literacy. To investigate this, we evaluated 8–12-year-old Spanish heritage speakers' (HSs) L1 production accuracy of grammatical gender and full verbal passives using picture description and elicited imitation (EI) tasks. One group of HSs attended bilingual (English-Spanish) schools and had developed strong L1 literacy skills; the other group attended English-only schools and had weaker L1 literacy skills, confirmed with standardized literacy tasks. The children receiving literacy instruction and textual exposure in Spanish (the L1) outperformed those attending schools in English only, producing gender agreement more accurately and full passives more accurately. They also outperformed the children in English-only schools in literacy and cognitive measures. These findings indicate that experience with textual input via L1 literacy development is an effective way to aid the acquisition and production of complex linguistic forms in HSs during the school-age period.